Chronic Intermittent Hypoxia-Induced Aberrant Neural Activities in the Hippocampus of Male Rats Revealed by Long-Term in vivo Recording - Xu, Linhao; Li, Qian; Ke, Ya; Yung, Wing-Ho (Frontiers in Cellular Neuroscience, 2022)
Chronic intermittent hypoxia (CIH) occurs in obstructive sleep apnea (OSA), a common sleep-disordered breathing associated with malfunctions in multiple organs including the brain. How OSA-associated CIH impacts on brain activities and functions leading to neurocognitive impairment is virtually unknown. Here, by means of in vivo electrophysiological recordings via chronically implanted multi-electrode arrays in male rat model of OSA, we found that both putative pyramidal neurons and putative interneurons in the hippocampal CA1 subfield were hyper-excitable during the first week of CIH treatment and followed by progressive suppression of neural firing in the longer term. Partial recovery of the neuronal activities was found after normoxia treatment but only in putative pyramidal neurons. These findings correlated well to abnormalities in dendritic spine morphogenesis of these neurons. The results reveal that hippocampal neurons respond to CIH in a complex biphasic and bidirectional manner eventually leading to suppression of firing activities. Importantly, these changes are attributed to a larger extent to impaired functions of putative interneurons than putative pyramidal neurons. Our findings therefore revealed functional and structural damages in central neurons in OSA subjects.